Heterotrophy in marine animal forests in an era of climate change - Denis, Vianney (2024)
Marine animal forests (MAFs) are benthic ecosystems characterised by biogenic three-dimensional structures formed by suspension feeders such as corals, gorgonians, sponges and bivalves. They comprise highly diversified communities among the most productive in the world's oceans. However, MAFs are in decline due to global and local stressors that threaten the survival and growth of their foundational species and associated biodiversity. Innovative and scalable interventions are needed to address the degradation of MAFs and increase their resilience under global change. Surprisingly, few studies have considered trophic interactions and heterotrophic feeding of MAF suspension feeders as an integral component of MAF conservation. Yet, trophic interactions are important for nutrient cycling, energy flow within the food web, biodiversity, carbon sequestration, and MAF stability. This comprehensive review describes trophic interactions at all levels of ecological organisation in tropical, temperate, and cold-water MAFs. It examines the strengths and weaknesses of available tools for estimating the heterotrophic capacities of the foundational species in MAFs. It then discusses the threats that climate change poses to heterotrophic processes. Finally, it presents strategies for improving trophic interactions and heterotrophy, which can help to maintain the health and resilience of MAFs.